2022
DOI: 10.18502/npt.v9i3.10227
|View full text |Cite
|
Sign up to set email alerts
|

Practice and associated factors of Glasgow Coma Scale assessment among nurses working in adult intensive care units of federally administered hospitals in Addis Ababa, Ethiopia

Abstract: Background & Aim: The Glasgow Coma Scale is a helpful instrument for measuring patients’ level of consciousness with neurosurgical disorders. Literature showed a majority of nurses don’t believe the Glasgow Coma Scale assessment is their area of practice. This study aimed to examine the Glasgow Coma Scale assessment practice and associated factors among nurses working in adult intensive care units of federally administered hospitals Methods & Materials: : Institutional-based cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Also, this finding consisted with a study finding in Egypt, to assess the knowledge, practice and identify the factors associated with assessment of the Glasgow Coma Scale among nurses which revealed the entire studied sample had unsatisfactory practice 5.7% and lack of training 5.1% (15) . This result agreed with a study in Addis Ababa to assess the knowledge, practice, and factors affecting GCS assessment among nurses which reported that nurses had low levels of knowledge and clinical practice about the Glasgow coma scale (16) . In researcher point of view the crowded patients and nursing shortage at emergency department may related to inadequate nurses practices.…”
Section: Discussion Nurses` Practices Toward Children With Chemical P...supporting
confidence: 89%
“…Also, this finding consisted with a study finding in Egypt, to assess the knowledge, practice and identify the factors associated with assessment of the Glasgow Coma Scale among nurses which revealed the entire studied sample had unsatisfactory practice 5.7% and lack of training 5.1% (15) . This result agreed with a study in Addis Ababa to assess the knowledge, practice, and factors affecting GCS assessment among nurses which reported that nurses had low levels of knowledge and clinical practice about the Glasgow coma scale (16) . In researcher point of view the crowded patients and nursing shortage at emergency department may related to inadequate nurses practices.…”
Section: Discussion Nurses` Practices Toward Children With Chemical P...supporting
confidence: 89%
“…Successful health service delivery is contingent on addressing all health system building blocks. However, there are multiple challenges, including low staff training levels; lack of essential equipment; and prohibitive out-of-pocket expenses [ 11 , 29 , 108 ] discussed further below. There are concerns that direct transplantation of critical care delivery models developed in high-income settings may neither be effective nor sustainable in lower-resourced settings [ 20 , 50 ].…”
Section: Definitionsmentioning
confidence: 99%